The Impact of Sustainable Transformational Leadership on Sustainable Innovation Ambidexterity: Empirical Evidence From Green Building Industries of China - Tang, Yuan; Chen, Yi-Jun; Shao, Yun-Fei; Cao, Qiao (Frontiers in Public Health, 2022)
Recognizing that building work will continually encompass, to a certain degree, unfavorable ecological consequences, green building has been encouraged and advocated as a managerial concept to progress in the construction segment. This research created a conceptual model that analyzed whether sustainable transformational leadership (STL) supported sustainable innovation ambidexterity (SIA) in green building industries. This research model was based on organizational support theory, hope theory, social cognitive theory, and attribution theory. This paper aimed to observe the relationship between STL with SIA via the mediating effect of psychological capital (PC). Furthermore, it examined the impact of perceived organizational support (POS) on PC. Moreover, it further examined the relationship between STL and POS. Likewise, it investigated the mediating effect of PC on the relationship between POS and SIA. Finally, it examined POS as a mediator between the relationship of STL and PC. The data for this study were collected from 600 workers employed at green building businesses in China. A questionnaire was delivered to the workers of green building corporations. According to the findings, STL was discovered to have a positive impact on PC. Furthermore, POS had a significant impact on PC. Moreover, PC significantly influenced SIA. Finally, STL was found to be in a significant relationship with POS. The outcomes of this research are extremely beneficial particularly in the situation of developing economies. This research contributes to the existing knowledge that employees with STL exhibit high PC, POS, and SIA in green building industries.